PENGARUH DIGITAL BANKING TERHADAP PROFITABILITAS DAN EFISIENSI OPERASIONAL PERBANKAN - Atasyadila, Hasna; Muchlis , Muchlis (Journal of Accounting, Management and Islamic Economics, 2024)
This study aims to determine whether the influence of Digital Bank on Return On Assets (ROA) or net profitability, determine whether the influence of Digital Bank on Net Interset Margin (NIM), and determine whether the influence of Digital Bank on BOPO. The method used in writing this final project is a quantitative method with the population used, namely Book III Conventional Banks and Book IV Banks during the 2016-2020 period with a total of 18 banks. This study uses the purpose method. sampling with statistical tests using the EViews10 program. The results of this study prove that Digital Banking has a positive and significant effect on ROA. The implementation of digital banking has resulted in increased bank profitability, due to an increase in the number of transactions through e-banking such as mobile and online transactions. Digital Banking also has a negative and significant effect on BOPO, which indicates a huge increase in efficiency in banking operations resulting from the application of digital banking. In addition, Digital Banking resulted in a decrease in NIM which indicated a decrease in the cost of intermediation that occurred in the banking industry due to the implementation of digital banking.